RETORIKA INFOGRAFIS PANDEMI CORONA VIRUS MEDIA JURNALISTIK DIGITAL ONLINE - Handriyotopo, Handriyotopo (Institut Seni Indoensia Surakarta, 2021)
AbstractThe phenomenon of infographics as a visual strategy to attract readers of digital newspapers in order to realize the importance of the protocol issued by WHO and the government of the Republic of Indonesia in an effort to deal with the Covid-19 pandemic, is currently quite prevalent by online media press. The visual form of infographics published by the digital-based press (online) is usually derived to accompany the main article on the front page (headline). The important message of the infographic that is prioritized is not to spread quickly, namely by maintaining social distancing, encouraging work at home, and always maintaining cleanliness and wearing a mask when leaving the house, even then with restrictions. How the form of visual communication design in the form of an infographic is able to provide aesthetic appeal in visual rhetoric to readers who will be the attention of this study. Through a qualitative research method approach to the phenomenon of infographic design from the perspective of text study from the aesthetic value of symbolic visual rhetoric with visual communication design analysis in terms of harmony achievement through its persuasive informative constituent elements. The findings of this study are related to the form of the infographic which is more portrait or vertical dominant. Colors tend to be strong colors red, yellow, blue, and black to indicate pandemic-related color psychology. Visual rhetoric tends to be iconic and header and copy letters are dominant in using sanserif to persuade understanding and reading of information to the reading audience. To remind adherence to health protocols, such as messages from mothers, namely wearing masks, washing hands and maintaining social distancing are the keywords to break this pandemic.Keywords: Covid-19 infographics, aesthetics, visual rhetoric, online press media